2014
DOI: 10.1515/jpem-2013-0366
|View full text |Cite
|
Sign up to set email alerts
|

Maternal factors and complications of preterm birth associated with neonatal thyroid stimulating hormone

Abstract: Thyroid hormones are important regulators of fetal neurodevelopment. Among preterm infants, TSH is highly variable. Understanding this variability will further improvements in screening for thyroid disorders in preterm infants. We examined 61 maternal and infant clinical and demographic factors for associations with neonatal TSH levels in 698 preterm neonates. TSH was measured as part of routine State-mandated newborn screening in Iowa. Of the maternal characteristics, nulliparous women (P=8x10−4), women with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
30
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 29 publications
10
30
0
4
Order By: Relevance
“…We cannot rule out the potential for null findings in our analyses of TSH being masked by high variability of newborn TH levels shortly after birth. It may be that screening data from even more than 48 hr are required to observe differences, though the trend towards earlier hospital discharge makes this challenging to address in more recent years [Rose et al, ; Ryckman et al, ; Shapira et al, ; Williams et al, ]. Large differences in the TSH‐ASD association by stratification factors were not suggested here.…”
Section: Discussionmentioning
confidence: 76%
“…We cannot rule out the potential for null findings in our analyses of TSH being masked by high variability of newborn TH levels shortly after birth. It may be that screening data from even more than 48 hr are required to observe differences, though the trend towards earlier hospital discharge makes this challenging to address in more recent years [Rose et al, ; Ryckman et al, ; Shapira et al, ; Williams et al, ]. Large differences in the TSH‐ASD association by stratification factors were not suggested here.…”
Section: Discussionmentioning
confidence: 76%
“…This combination has expanded the novel application of linking newborn screening results to acquired newborn disease. (36, 37) Our study population included preterm infants from across the broad geographic and socioeconomic regions of California and the results remained robust while controlling for multiple patient demographic factors. In light of these strengths it should also be recognized that there are important limitations to the present study.…”
Section: Discussionmentioning
confidence: 81%
“…However, in 2013, Torkaman et al [8] reported the association with RDS while analyzing the TSH and free T 4 in premature infants, and in 2014, Ryckman et al [9] reported that there is a strong association between thyroid stimulating hormone and RDS. In addition, Tanaka et al [10] reported in 2007 that the TSH surge caused by the stress during birth improves surfactant production.…”
Section: Introductionmentioning
confidence: 99%